Research Studyof Intrinsic and Extrinsic Learning Motivation Physical Education - Vai, Aref; Wijayanti, Ni Putu Nita; Juita, Ardiah; Sulastio, Agus; Aspa, Agus Prima; Adila, Fekie (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2022)
The success of physical education learning is influenced by several factors, namely physical, cognitive and psychological skills. Psychological skills based on literature studies are an important component that has become the focus of research, especially on aspects of students' learning motivation. This study aims to reveal the psychological skills in physical education learning about intrinsic and extrinsic motivation that affect the success of the type of research used is a literature study or commonly called a literature study. Literature review is part of a qualitative research in which the analysis of research data is based on a data set of published articles that discuss intrinsic and extrinsic motivation in physical education learning. Data analysis is based on a collection of articles published in journals in the last 10 years. The results of the literature review are expected to be used as studies or information that can be used as a theoretical basis for further research in the use of intrinsic and extrinsic motivation to support physical education learning success.